A COMPARATIVE STUDY OF PRINCIPALS’ LEADERSHIP BEHAVIORS AND SCHOOL CLIMATES OF TWO INTERNATIONAL ELEMENTARY SCHOOLS IN YANGON, MYANMAR - Lei Phyu, Seinn; Vinitwatanakhun, Watana (Scholar: Human Sciences, 2015)
The purpose of this study was to: (1) identify the teachers’ perceptions of their principals’ leadership behaviors from two international elementary schools in Yangon, Myanmar, (2) identify the teachers’ perceptions of their school climates, and (3) compare the principals’ leadership behaviors and school climates perceived by teachers. Theories that were supportive in this study are (1) Path-Goal Theory of Leadership which was developed by House and his colleagues in the early 1970s, (2) Organizational Climate theories such as “The Mechanistic, Bureaucratic Model” and “The Organic, Humanistic Model” which were conducted by Owens and (3) The School Climate Model by Hoy et.al (1996). The revised Organizational Climate Description Questionnaires (OCDQ- RE) were used as instrumental tool to meet the research objectives in this investigation and they were distributed to 59 teachers from two international elementary schools in Yangon in May, 2013. The rating scale for level of practice was a four-point Likert Scale and frequencies, percentages, means, and two-tailed independent sample t-test were the statistical techniques applied in data analysis. Regarding to the results from the data analysis, it was found out that most teachers perceived their principals’ leadership behavior as supportive as high in both schools. Teachers also perceived their leadership behavior by themselves as collegial as high in both schools. Hence principals’ leadership behaviors were surveyed as supportive as high and teachers’ leadership behaviors were surveyed as collegial, principals-teachers and teachers-teachers relationships could be interpreted as open and teachers perceived their school climates as open climates. There is no difference between school climates perceived by teachers between School A and School B in Yangon, Myanmar.